Higher Education Teachers' Perception and Use of Project-Based Learning in Teaching English - Lengkoan, Fergina; Basri, Muhammad; Nur, Sahril; Ali, Nornazurah Nazir; Maru, Mister Gidion (Jurnal Lingua Idea, 2024)
This study aims to examine how English professors perceive adopting project-based learning and examine the difficulties they encounter when doing so in various colleges. All the research subjects used four sources of English language education study programs. The study included all instructors who had used project-based learning in their classes. A questionnaire was used to gather quantitative data for this investigation. The study's findings indicate that English teachers positively view project-based learning. Teachers are eager to integrate Project-Based Learning if they have a favourable opinion quickly. The challenges were finding resources to help students with their projects and running out of time to finish them. The following suggestions urge more significant investigation into potential solutions to overcome project-based learning's adoption challenges, particularly in teaching English.